Objects, Components and the Virtual Enterprise - Nixon, Patrick; Dobson, Simon (Trinity College Dublin, Department of Computer Science, 1999)
We are currently witnessing a convergence of several threads of technology and business imperatives. The idea of a virtual enterprise (VE) ? a business built from both organizationally and geographically distributed units ? is becoming an area of increasing interest to both computer scientists and business people. The Objects, Components and the Virtual Enterprise workshop at OOPSLA 98 investigated the role of Object/Component analysis, design and programming in the realization of the VE. The workshop addressed topics including lifecycle models, case studies, HCI, object renaming, and software architectures VEs.
Keywords: Computer Science